Arithmetic of Finite Fields Third International Workshop, WAIFI 2010, Istanbul, Turkey, June 27-30, 2010. Proceedings - Hasan, M. Anwar.; Helleseth, Tor. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the Third International Workshop on the Arithmetic of Finite Fields, WAIFI 2010, held in Istanbul, Turkey, in June 2010. The 15 revised full papers presented were carefully reviewed and selected from 33 submissions. The papers are organized in topical sections on efficient finite field arithmetic, pseudo-random numbers and sequences, Boolean functions, functions, Equations and modular multiplication, finite field arithmetic for pairing based cryptography, and finite field, cryptography and coding.